Implementasi Metode Design Thinking Pada Perancangan User Interface Aplikasi Rumah Baca Cerdas Library Mobile - Dinda Puspa Aprilia; Aminudin, Aminudin (STMIK Budi Darma, 2024)
The digitalization era has transformed many systems into digital, including the digitalization of libraries. The use of library applications aims to facilitate users in borrowing books and other processes. However, in the use of the library website owned by RBC Institute, there is a gap between user needs and user experience. Therefore, the aim of this study is to design a library application that meets user needs by applying the Design Thinking method. This method allows designers to understand user needs and desires, so that the resulting application can meet user expectations. In addition to applying the Design Thinking method, this study also uses the System Usability Scale method to test the design solutions that have been made. The results obtained are 9 display menus and an SUS score of 84.5. The results of the study are expected to meet user needs and ease of use, thus creating a good user experience and can be used as a design in developing the RBC Library application